Ring-theoretic properties of Iwasawa algebras: a survey - Ardakov, K; Brown, K (Universität Bielefeld, 2006)
This is a survey of the known properties of Iwasawa algebras, which are completed group rings of compact p-adic analytic groups with coefficients the ring Zp of p-adic integers or the field Fp of p elements. A number of open questions are also stated.